Information resources in toxicology. - Wexler, Philip, 1950- (Academic/Elsevier, 2009)
This latest version of Information Resources in Toxicology (IRT) continues a tradition established in 1982 with the publication of the first edition in presenting an extensive itemization, review, and commentary on the information infrastructure of the field. This book is a unique wide-ranging, international, annotated bibliography and compendium of major resources in toxicology and allied fields such as environmental and occupational health, chemical safety, and risk assessment. Thoroughly updated, the current edition analyzes technological changes and is rife with online tools and links to Web sites. IRT-IV is highly structured, providing easy access to its information. Among the "hot topics" covered are Disaster Preparedness and Management, Nanotechnology, Omics, the Precautionary Principle, Risk Assessment, and Biological, Chemical and Radioactive Terrorism and Warfare are among the designated. .International in scope, with contributions from over 30 countries .Numerous key references and relevant Web links .Concise narratives about toxicologic sub-disciplines .Valuable appendices such as the IUPAC Glossary of Terms in Toxicology .Authored by experts in their respective sub-disciplines within toxicology